Safe fluoroquinolones prophylaxis in blood cancer patients with chemotherapy‐induced neutropenia and Glucose‐6‐Phosphate‐Dehydrogenase deficiency. (8th June 2017) - Sanna, M.; Caocci, G.; Orrù, F.; Ledda, A.; Vacca, A.; Piras, E.; Fozza, C.; Deias, P.; Tidore, G.; Dore, F.; La Nasa, G.
Summary: What is known and objective: Bacterial infections are the leading causes of morbidity and mortality in haematologic patients with chemotherapy‐induced neutropenia. The only strategy shown to be effective in reducing febrile neutropenia incidence is fluoroquinolone prophylaxis, but the safety of this class of drugs in patients with glucose‐6‐phosphate dehydrogenase deficiency (G6PD−), the most common human enzyme defect, is still controversial because of the claimed association with acute haemolytic anaemia. Methods: We retrospectively analysed 242 patients treated with 628 intensive chemotherapy courses. Of these, 59 patients were with G6PD−. All patients underwent fluoroquinolone prophylaxis and were transfused according to our single‐unit transfusion policy. The principal endpoint was the incidence of acute haemolytic anaemia. Secondary endpoints included the incidence of febrile neutropenia, microbiologically and clinically documented infection (MDI and CDI) and the incidence of Gram‐positive or Gram‐negative infections. Results and discussions: No episode of acute haemolytic anaemia was observed in the entire cohort. The incidence of MDI and CDI was similar, but the incidence of invasive fungal disease (IFD; P <.0001, HR 11.4, 95%CI 3.5‐37.05) and Candida sepsis ( P =.008, HR 37, 95%CI 2.01‐680.9) was higher in patients with G6PD−. Interestingly, we observed a reduced incidence of febrile neutropenia in patients with G6PD− ( P =.01, HR 0.46, 95%CI 0.25‐0.8). What is new and conclusions: Our data suggest that fluoroquinolone prophylaxis in patients with G6PD−, treated with intensive chemotherapy, is feasible and safe. Our findings on the incidence of IFD and febrile neutropenia suggest that G6PD may be important in susceptibility to opportunistic pathogens and host response in neutropenic patients. Abstract : Fluoroquinolone prophylaxis in patients with Glucose‐6‐Phosphate Dehydrogenase (G6PD) deficiency treated with intensive chemotherapy is feasible and safe. Our findings in terms of incidence of invasive fungal disease and febrile neutropenia focus the light on G6PD as an important player in susceptibility to opportunistic pathogens and host response in neutropenic patients.